Socio-Economic Status of Women Volleyball Players in Nepal - Pant, Kumari Hira; Baruwal, Hum Bahadur; Acharya, Bidhan (Journal of Research in Education, 2025)
The study analyzed socioeconomic status of seventy-five Nepali women volleyball players aged 14-39 from the National team and five clubs. Structured questionnaire and interviews were employed to collect qualitative and quantitative data on ethnic background, religion, income and education level, and satisfaction with the game of the respondents. The findings revealed that Brahman and Chhetri (50.7%) players had the highest participation, followed by Janajati (42.6%) and Dalits (6.7%). The largest representation of national-level clubs was from Sudur Paschim Province. Among employed players, an average monthly income varied from NRS 25,000 to NRS 30, 000. The highest average income was earned by older players (30+ years), while the lowest average income was earned by younger players (14-19 years). There was a positive relationship between experience and monthly income. The average age of the volleyball players was 22.8 years, with 45.3% in the 20-24 age group, which corresponds to volleyball's prime athletic years. Regarding education, 48.0% of the players had completed SEE, 42.7% had a plus-two education, while 5.3% had earned a bachelor's degree. Analysis of societal perception before and after starting volleyball did not show a significant difference. The results showed that the majority of the parents lacked formal education and depended on agriculture, indicating a strong rural and agriculture-based socioeconomic background. The study shows potential in women’s volleyball in Nepal to provide several opportunities for youths and emphasizes the need for support at the household, community, institutional and policy levels.